CLIMATE MIGRATION AND ECOLOGICAL REFUGEES: A GLOBAL ISSUE AND ITS SOCIO-ECONOMIC IMPACT - Bekzod Umarov Baxtiyorjon o‘g‘li, Xomidov Xolmurod Muydinovich, Isroilov Zafarjon Nizomitdin o‘g‘li (Ethiopian International Journal of Multidisciplinary Research, 2026)
This scientific article provides a comprehensive analysis of migration processes arising as a result of climate change. It explores the theoretical foundations of climate migration, as well as the formation and development stages of the ecological refugee phenomenon. Based on global and regional statistical data, the study evaluates the demographic, economic, and social consequences of climate change.